MODELS AND INFORMATION SYSTEMS OF ECOLOGICAL AND ECONOMICAL RISKS WITH DECISION MAKING ON THE CLOSURE OF COAL MINES - ALEKSIEIEV, Mykhailo; VLASOV, Vladyslav (My University, 2018)
Development of decision support system based on simulation results of underworking of surface and selection of rational way of remediation.